Pregnane X receptor reduces particulate matter-induced type 17 inflammation in atopic dermatitis - Lee, Ji Su; Lee, Youngae; Jang, Sunhyae; Oh, Jang-Hee; Lee, Dong Hun; Cho, Soyun (Frontiers in Immunology, 2024)
Background Epidemiological evidence suggests that particulate matter (PM) exposure can trigger or worsen atopic dermatitis (AD); however, the underlying mechanisms remain unclear. Recently, pregnane X receptor (PXR), a xenobiotic receptor, was reported to be related to skin inflammation in AD. Objectives This study aimed to explore the effects of PM on AD and investigate the role of PXR in PM-exposed AD. Methods In vivo and in vitro AD-like models were employed, using BALB/c mice, immortalized human keratinocytes (HaCaT), and mouse CD4+ T cells. Results Topical application of PM significantly increased dermatitis score and skin thickness in AD-like mice. PM treatment increased the mRNA and protein levels of type 17 inflammatory mediators, including interleukin (IL)-17A, IL-23A, IL-1β, and IL-6, in AD-like mice and human keratinocytes. PM also activated PXR signaling, and PXR knockdown exacerbated PM-induced type 17 inflammation in human keratinocytes and mouse CD4+ T cells. In contrast, PXR activation by rifampicin (a human PXR agonist) reduced PM-induced type 17 inflammation. Mechanistically, PXR activation led to a pronounced inhibition of the nuclear factor kappa B (NF-κB) pathway. Conclusion In summary, PM exposure induces type 17 inflammation and PXR activation in AD. PXR activation reduces PM-induced type 17 inflammation by suppressing the NF-κB signaling pathway. Thus, PXR represents a promising therapeutic target for controlling the PM-induced AD aggravation.